Searching for welfare, work and gender equality - Janneke Plantenga (WWWforEurope, 2014)
The paper describes to which extent European welfare states support an individual adult worker model and how the current policy should be assessed in terms of gender equality. Although a more individual design of welfare policies is clearly recognizable, the paper also illustrates the large gap between the implicit assumptions of the adult worker model and the actual reality of most European Member States. Only a few countries, with the Nordic countries as the most well-known examples, have developed a system of child care arrangements that seems to be based on the assumption that fathers and mothers will both be fully engaged in the labour market. Others countries have invested in policies which allow for large interruption in labour force participation or which allow the combination of work and care by introducing part-time working hours. Overall the actual policy design does not indicate a high profile of gender equality. Perhaps the most challenging problem of the current redesign of the welfare state is that family support policies can only to a certain extent been redesigned in accordance with employment policies. Although some women participate on an equal footing with men, the dual earner, gender specialized, family model, which is geared towards greater, but not full equality, seems more feasible.
Keywords: J13; J16; J22; H31; I38; 330; Labour force participation; gender equality; government policy; fiscal policy; child care